A Damage Sensor Associated with the Cuticle Coordinates Three Core Environmental Stress Responses in Caenorhabditis elegans. Issue 4 (1st April 2018) - Dodd, William; Tang, Lanlan; Lone, Jean-Christophe; Wimberly, Keon; Wu, Cheng-Wei; Consalvo, Claudia; Wright, Joni E; Pujol, Nathalie; Choe, Keith P
Abstract: Although extracellular matrices function as protective barriers to many types of environmental insult, their role in sensing stress and regulating adaptive gene induction responses has not been studied carefully... Extracellular matrix barriers and inducible cytoprotective genes form successive lines of defense against chemical and microbial environmental stressors. The barrier in nematodes is a collagenous extracellular matrix called the cuticle. In Caenorhabditis elegans, disruption of some cuticle collagen genes activates osmolyte and antimicrobial response genes. Physical damage to the epidermis also activates antimicrobial responses. Here, we assayed the effect of knocking down genes required for cuticle and epidermal integrity on diverse cellular stress responses. We found that disruption of specific bands of collagen, called annular furrows, coactivates detoxification, hyperosmotic, and antimicrobial response genes, but not other stress responses. Disruption of other cuticle structures and epidermal integrity does not have the same effect. Several transcription factors act downstream of furrow loss. SKN-1 /Nrf and ELT-3 /GATA are required for detoxification, SKN-1 /Nrf is partially required for the osmolyte response, and STA-2 /Stat and ELT-3 /GATA for antimicrobial gene expression. Our results are consistent with a cuticle-associated damage sensor that coordinates detoxification, hyperosmotic, and antimicrobial responses through overlapping, but distinct, downstream signaling.